Political Party Diplomacy with Chinese Characteristics in Seven Decades since Founding of PRC - Shi, Xiaohu (Napredak, 2021)
Since the founding of the People`s Republic of China, the Communist Party of China has found itself in a complicated international situation and arduous development tasks. The CPC has steadily promoted its foreign exchanges in the process of inheritance and development. It has achieved leaps in practice of the theoretical innovations in party to party diplomacy with Chinese characteristics, which contributed significantly to the central missions of the Party and the nation, as well as the overall strategy of the state diplomacy. Starting at a new historical phase, it is crucial to summarize the experience of the practical and theoretical innovations in party to party diplomacy with Chinese characteristics. It is also of great importance to discover the basic logic and principles therein. All of which would provide practical significance for promoting a benign interaction between the practice and theory of party to party diplomacy, and make greater contribution.